PERFECTION OF ORGANIZATIONAL AND ECONOMIC MECHANISMS TO CONTROL SERVICE SECTOR IN THE STIPULATION OF DIGITAL VARIATIONS IN THE ECONOMY UZBEKISTAN - Xonkeldieva, G.Sh.; Shanazarova, Gulyorahon Bakhtiyarovna (The journal of contemporary issues in business and government, 2021)
The article discusses the improvement of organizational and economic control mechanisms of the service sector while stimulating digital changes in the economy of Uzbekistan. It also pays attention to a number of areas of modernization services and analyzes all aspects of the research process that has made significant progress in this area in recent years.